Prognostication of air pollution effect on the morbidity of the population in the industrial city - Hrebniak, M.P.; Fedorchenko, R.A. (Environment & Health, 2016)
Objective. We substantiated the prognostication model of the effect of the industrial emissions on the morbidity of the population.Materials and methods. Total emissions in the ambient air of megalopolis, indices of the morbidity of the population, correlative-and- regressive analysis.Results. We determined a character of the correlation of the industrial emissions and the level of the use of the production capacities. The step-by-step regressive models of the prognostication of the morbidity of respiratory diseases were substantiated taking into account a character of air pollution. The volumes of the emissions of ammonia, styrene, phenol, sulfuric acid and nitric acid, hydrogen sulfide, toluene in the air are the prior ones for the morbidity and prevalence of respiratory diseases. From the concentrations phenol, nitrogen dioxide, hydrogen chlorides and fluorides are prognostically significant. Practical testing of the developed models both for adults and children indicates a presence of a very high correlation with emissions, a high correlation with the concentrations and points to a high reliability of the prognostication of morbidity (87.7-91.6%, p
Keywords: air pollution; morbidity; respiratory diseases; step-by-step regressive model